STUDENTS’ BELIEF ON LEARNING AS A FOREIGN LANGUAGE AT SOCIAL SCIENCE DEPARTMENT - Autila, Rani; Merina, Yola; Sevrika, Hevriani (TELL - US JOURNAL, 2021)
This research investigated students’ belief on learning English as a foreign language at Social Science Department of STKIP PGRI Sumatera Barat. Based on the learner-centered approaches to foreign language teaching, it is important for teacher to understand about students’ prior knowledge and experiences, expectations, and attitudes towards language learning. Belief as part of attitude can influence students’ way of thinking, feeling, or making sense of the learning process. Thus, the teachers need to know about students’ belief. The purpose was to find what beliefs about language learning do Social Science Department students hold? The methodology of research is descriptive quantitative research. It describes the phenomena about students’ belief in the field. This study examines all students in Social Science Department of STKIP PGRI Sumatera Barat which totally 10 students. The data were taken form a questionnaire. The findings of the research showed that English subject in campus is not enough for students to develop their English ability. However, they belief that they have a special ability in learning English. The results also showed that some students have belief which in learning English students have to know the culture of the native speaker, have good grammar, pronunciation and practice regularly.